Accelerated partial breast irradiation in clinical practice - Wenz, Frederik; Herskind, Carsten; Welzel, Grit; Sperk, Elena; Gauter-Fleckenstein, Benjamin; Sütterlin, Marc (Breast care, 2015)
Accelerated partial breast irradiation (APBI) has been under clinical investigation for more than 15 years. There are several technical approaches that are clinically established, e.g. brachytherapy,